Higher Education as a Gift and as a Commons - Andreas Wittel (tripleC: Communication, Capitalism & Critique)
This paper takes as a starting point Lewis Hyde’s (2007, xvi) assertion that art is a gift and not a commodity: “Works of art exist simultaneously in two ‘economies’, a market economy and a gift economy. Only one of these is essential, however: a work of art can survive without a market, but where there is no gift there is no art.” I want to argue that the same claim should be made for those aspects of academic labour that refer to teaching and education. Education can survive without a market, but where there is no gift there is no education. However the gift that is part of all educational processes gets rather obscured in regimes where higher education is either a public good or a private good. In regimes of higher education as public good the gift gets obscured by the provision of a service by the state. In regimes of higher education as a private good (e.g. higher education in the UK) the gift gets even more obscured, obviously so. It is only in a third educational regime, where education is a common good (e.g. the recent rise of the free universities), that the gift character of education can properly shine. Whilst this should be celebrated, the notion of a higher education commons poses some severe challenges. The paper ends with an examination of possibilities of academic activists to rescue or even strengthen the gift-like character of education.